DYNAMIC MUSCULAR ENDURANCE IN CONNECTION WITH THE STATE OF PSYCHOPHYSIOLOGICAL FUNCTIONS OF QUALIFIED FEMALE ATHLETES - ФЕДОРЧУК, С.; ПЕТРУШЕВСЬКИЙ, Є. (Київський національний університет імені Тараса Шевченка, 2020)
The aim of the study was to determine the relationship between dynamic muscular endurance of the hand (according to the tapping test) with the state of psychophysiological functions of qualified female handball players at different stages of sports training. Diagnostic complex "Diagnostics-1" (MV Makarenko, VS Lyzogub) was used to determine the state of psychophysiological functions of athletes, the maximum rate of movement of the brush. Dynamic muscular endurance of the right and left brushs, properties of the nervous system (functional mobility and strength of nervous processes), the effectiveness of sensorimotor activity and the dynamics of nervous processes, the latency period of a complex reaction of choice, the accuracy of the reaction to a moving object were studied in accordance with the purpose of the study. Dynamic muscular endurance of subdominant hand was significantly higher in older female athletes. There is a tendency to increase the dynamic muscular endurance of the dominant hand in older female athletes. The asymmetry according to the indicators of the tapping test between the right and left hand was lower in the older age group than in the younger age group. In general, the results indicate a higher level of dynamic muscular endurance of both arms in older female athletes, who are more adapted to long-term specific physical activity. That is, the improvement of special training in handball leads to the development of dynamic muscular endurance. This is confirmed by the results of the correlation analysis of the obtained data: dynamic muscular endurance of the subdominant arm was associated with the experience of sports training. The maximum rate of movement of the brush of both hands in the surveyed female athletes was associated with the strength of nervous processes and the accuracy of the reaction to a moving object. The dynamic muscular endurance of the dominant hand' brush was associated with the functional mobility of nervous processes.

Метою дослідження було визначення зв'язків динамічної м'язової витривалості руху кисті (за показниками тепінгтесту) зі станом психофізіологічних функцій кваліфікованих гандболісток на різних етапах спортивної підготовки. Для визначення стану психофізіологічних функцій спортсменок, максимального темпу руху кисті використовували діагностичний комплекс "Діагност-1" (М. В. Макаренко, В. С. Лизогуб). Відповідно до мети роботи у спортсменок досліджувалися: динамічна м'язова витривалість правої і лівої кистей, властивості нервової системи (функціональна рухливість і сила нервових процесів), ефективність сенсомоторної діяльності й динамічність нервових процесів, латентний період складної реакції вибору, точність реакції на рухомий об'єкт. Динамічна м'язова витривалість руху кисті субдомінантної руки була значуще більша у спортсменок старшої вікової групи. Виявлено тенденцію до збільшення динамічної м'язової витривалості руху кисті домінантної руки у спортсменок старшої вікової групи. Асиметрія за показниками тепінг-тесту між правою та лівою руками у спортсменок старшої вікової групи була менша, ніж у спортсменок молодшої вікової групи. Отримані результати вказують на вищий рівень динамічної м'язової витривалості обох рук у спортсменок старшої вікової групи, які більш адаптовані до довготривалих специфічних фізичних навантажень. Тобто удосконалення спеціальної підготовленості в гандболі приводить до розвитку динамічної м'язової витривалості. Це підтверджують результати проведеного кореляційного аналізу отриманих даних: динамічна м'язова витривалість субдомінантної руки асоціювалася зі стажем спортивного тренування. Максимальний темп руху кисті обох рук був пов'язаний із силою нервових процесів і точністю реакції на рухомий об'єкт. Динамічна м'язова витривалість кисті домінантної руки була пов'язана з функціональною рухливістю нервових процесів.
ДИНАМІЧНА М'ЯЗОВА ВИТРИВАЛІСТЬ У ЗВ'ЯЗКУ ЗІ СТАНОМ ПСИХОФІЗІОЛОГІЧНИХ ФУНКЦІЙ КВАЛІФІКОВАНИХ СПОРТСМЕНОК
Keywords: dynamic muscular endurance; tapping test; state of psychophysiological functions; highly qualified female athletes; handball; динамічна м'язова витривалість; тепінг-тест; стан психофізіологічних функцій; спортсменки високої кваліфікації; гандбол; Біологія